A titanium nitride nanotube array for potentiometric sensing of pH. Issue 5 (28th January 2016) - Liu, Mengyang; Ma, Yanling; Su, Lei; Chou, Kuo-Chih; Hou, Xinmei
Abstract : A titanium nitride nanotube array (TiN NTA) was fabricated through reduction and nitridation of TiO2 NTA obtained from anodic oxidation of titanium. Abstract : A titanium nitride nanotube array (TiN NTA) electrode was fabricated through anodic oxidation of titanium and reduction and nitridation of TiO2 NTA. The microstructure of TiN NTA was characterized to be uniform with inner diameters of about 120 nm, a wall thickness of 15–20 nm and an average length of 10 μm. Open-circuit potentials were measured to evaluate the TiN TNA electrode related to pH sensitivity, response time, stability, selectivity, hysteresis and reproducibility in the pH range of 2.0–11.0 at 20 ± 1 °C. The prepared TiN NTA electrode exhibits a near-Nernstian slope of 55.33 mV per pH with the correlation coefficient value of 0.995. It shows good selectivity for H + ions in the presence of cations and anions, especially in fluoride-containing media. It also has good stability and reproducibility with a response time of 4.4 s. These make it a promising candidate as a pH electrode sensor.